Desperate Times Call for Desperate Measures: Crime in Wabaunsee Township, Wabaunsee County, Kansas 1858-1921 - Melby, Aaron (Kansas State University, The Chapman Center for Rural Studies, 2012)
This study uses two Justice of the Peace record books to correlate patterns in early Wabaunsee Co., crime rates with major regional and national events. The results of this study show spikes in crime rates following events that put strain on the United States economically and socially. These spikes show economic and social stress in an area that otherwise had relatively low amounts crime.
Aaron Melby, “Desperate Times Call for Desperate Measures: Crime in Wabaunsee Township, Wabaunsee County, Kansas 1858-1921,” Chapman Center Research Collections, accessed November 11, 2020, https://ccrsresearchcollections.omeka.net/items/show/219.
Keywords: Wabaunsee County; Zeandale Township; Wabaunsee Township; Panic of 1873; Gary Lafree; E.R. McCurdy